FINANCIAL LITERACY AND FINANCIAL INCLUSION ON SUSTAINABLE CREDIT DECISIONS THROUGH FINANCIAL BEHAVIOR : A STUDY OF MERAUKE MSMES - Ni Luh Putu Nita Yulianti; Adi Maulana Rachman; Caecilia Henny Setya Wati; Yumiad Fernando Richard (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2025)
Study This aim For analyze impact financial literacy and financial inclusion to taking decision sustainable credit​ through Financial behavior of MSMEs in Merauke City. Problems study leave from low financial literacy perpetrator business as well as limited utilization service formal finance, which causes decision credit often taken without careful consideration. Research​ This use method quantitative with population as many as 3.777 MSMEs. The sampling technique sample done with purposive sampling and quota sampling methods, with amount respondents as many as 120 MSMEs in Merauke City. Data collected through questionnaire Likert scale, then analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS). The research results show that financial literacy No influential significant to taking decision credit sustainable. Financial inclusion also not influential significant to sustainable credit decisions. On the other hand, financial behavior proven influential positive and significant to decision credit sustainable. Furthermore, the results of the mediation test show that financial literacy and financial inclusion influential No direct to decision credit sustainable through financial behavior. Findings This confirm that understanding and access finance Not yet Enough push decision sustainable credit​ if No reflected in financial behavior everyday. Therefore, literacy and inclusion programs are needed finances that are not only emphasize aspect knowledge, but also formation behavior healthy finances among Merauke MSMEs.